2008
DOI: 10.1016/j.mrfmmm.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent reduction of 3,2′-dimethyl-4-aminobiphenyl-derived DNA adducts in colon and liver of rats administered celecoxib

Abstract: Colon cancer is second leading cause of cancer-related deaths in Western countries. Diet and smoking, which contain aromatic and heterocyclic amines, are major risk factors for colon cancer. Colorectal cancers have a natural history of long latency and therefore provide ample opportunities for effective chemoprevention. 3,2'-Dimethyl-4-aminobiphenyl (DMABP) is an experimental aromatic amine that causes cancer in rat colon and serves as an experimental model for arylamine and heterocyclic amine mutagens derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a case-control study, heterocyclic amines were associated with risk of colorectal adenomas (48). Interestingly, the COX-2 selective NSAID celecoxib has been shown to decrease heterocyclic amine-induced colonic mutagenicity in experimental rats (49). Late effects on CRC progression or survival attributed to these carcinogenic agents are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, heterocyclic amines were associated with risk of colorectal adenomas (48). Interestingly, the COX-2 selective NSAID celecoxib has been shown to decrease heterocyclic amine-induced colonic mutagenicity in experimental rats (49). Late effects on CRC progression or survival attributed to these carcinogenic agents are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Docosahexanenoic acid treatment reduced formation and growth of 2-amino-1-methyl-6phenylimidazo(4,5-b) pyridine-induced ACF in rat colon (32). Recently, celecoxib was shown to reduce DNA adduct levels in colon of rats treated with DMABP (33). Thus, we hypothesized that sulindac and celecoxib as inhibitors of COX-1 and/or COX-2 would reduce colon AC/ACF resulting from exposure to DMABP.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that diets containing wheat bran and citrus fiber reduce the risk for DMAB-induced intestinal cancer and that the protection against CRC depends on the type of fiber. DMAB reacts with DNA through the formation of DNA adducts via N-hydroxylation, O-acetylation, and hydrolysis by cytochrome P450 [59].…”
Section: Aromatic Aminesmentioning
confidence: 99%